The Gendered Burdens of Conviction and Collateral Consequences on Employment - Erin E. Meyers (2019)
Ex-offenders are subject to a wide range of employment restrictions that limit the ability of individuals with a criminal background to earn a living. This Article argues that women involved in the criminal justice system likely suffer a greater income-related burden from criminal conviction than do men. This disproportionate burden arises in occupations that women typically pursue, both through formal pathways, such as restrictions on occupational licensing, and through informal pathways, such as employers’ unwillingness to hire those with a criminal record. In addition, women have access to far fewer vocational programs while incarcerated. Further exacerbating this burden is that women involved in the criminal justice system tend to be a more vulnerable population and are more likely to be responsible for children than their male counterparts, making legal restrictions on access to public assistance that would support employment more burdensome for women. We propose programs and policies that may ameliorate these gendered income burdens of criminal conviction, including reforms to occupational licensing, improved access to public assistance, reforms to prison labor opportunities, improvements in labor market information sharing, and expanded employer liability protection